Parental Depressive Feelings, Parental Support, and the Serotonin Transporter Gene as Predictors of Adolescent Depressive Feelings: A Latent Growth Curve Analysis - van Roekel, Eeske (Springer US, 2010)
Parental support and parental depressive feelings are found to be associated with depressive feelings in adolescent boys and girls, but results are inconsistent. In addition, the 5-HTTLPR genotype has been found to interact with environmental stressors in predicting adolescents’ depressive feelings, but this has not been examined longitudinally. Therefore, the present study examined the relationships between parental support, parental depressive feelings, and adolescent depressive feelings. In addition, the relationships between the 5-HTTLPR genotype and adolescent depressive feelings were explored, as well as gene-environment interactions. Adolescents (N = 306; Girls = 53.3%; M (age T1) = 13.4) filled out questionnaires at five annual waves and provided saliva samples for DNA. Latent growth curve modelling (LGCM) was used to examine the baseline level and the change in depressive feelings over time. Maternal support was related to baseline levels of depressive feelings in girls, whereas paternal support was related to baseline levels in boys. Paternal depressive feelings were only related to boys’ depressive feelings at baseline, and maternal depressive feelings were not related to any outcome measures. Furthermore, no associations were found between 5-HTTLPR genotype and adolescent depressive feelings, and no gene-environment interactions emerged. Limitations of the study and implications of the findings are discussed.